IDENTIFICATION OF FORMS FUNDAMENTALERRORS IN DURING THE PROCESS OF SOLVING CALCULUS PROBLEMS I BY INFORMATICS ENGINEERING STUDENTS - Kennedi Tampubolon; Chandra F.Sianturi (Jurnal Scientia, 2021)
One of the problems faced by Students of Informatics Engineering, BUDI DARMA Medan Semester I is the lack of ability of students in solving basic Calculus problems due to the lack of knowledge to analyze, model and manipulate the forms of problems from verbal language forms into simpler forms of Mathematics language. This problem has an impact on the low grades of UTS and UAS CALCULUS courses obtained by students so that it becomes a serious problem that can inhibit the development of cognitive ability in solving calculus problems. To find out the root of the problem experienced by students, researchers conduct research. To get research data, researchers conduct evaluations of students by giving a Test Description. Because the situation is still during the COVID-19 pandemic, researchers gave an evaluation in the form of Online Test via Google Classroom with sub Classwork. This research is intended to identify technical errors made by students when completing the description problem. While the approach taken in this study is a descriptive qualitative and quantitative approach. The subject of the study was a Student of Semester II of Informatics Engineering, Budi Darma Medan T.A 2020/2021. The research instrument that is built is a Problem Description where each point of the problem contains the nature and basic law of Arithmetic Calculation Operation or Algebra as the basic or basic lmu calculus. Furthermore, the Researcher makes corrections, analyzing data related to errors made during the problem resolution process. The results of the study are poured in the form of error classification tables for further data obtained processed using descriptive statistical methods. The results of data processing obtained in the form of statistical data are presented specifically and listed on tables and diagrams that form the basis in the withdrawal of conclusions.